(untitled) (Biological Sciences - PJSIR, 2004)
The production of ice being sold in the local market of Karachi is neither regulated nor its quality and safety for human consumption is evaluated. This investigation examined the physico-chemical and bacteriological characteristics of 50 ice samples collected from different areas of Karachi city. The water being used for ice manufacturing is of poor quality, almost all the samples were found unsafe as per WHO guidelines for safe drinking water; total bacterial count exceeded the upper limit 100 CFU/mL, forty one samples out of fifty had high coliform and faecal coliform counts. The ice produced in the city by commercial manufacturers is of very poor microbiological quality and its consumption pose an immediate threat to public health. The potential for disease exists in the ice industry of Pakistan which demands special need for the implementation of appropriate remedial measures to ensure that ice produced and sold in the market is safe for human consumption.